(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
In this work, using modern physicochemical research methods, the interaction of various amino acid solutions with the Cu(II) ion, the structure and properties of the resulting complex compounds were studied. The influence of the environment on the formation of pure and mixed ligand complexes from various obtained amino acids and the constants of stability and instability were determined.